KARAKTERISTIK PENGERINGAN CHIPS MANGGA MENGGUNAKAN KOLEKTOR SURYA KACA GANDA [Characteristics of Mango Chips Drying Using a Double Plated Solar Collector] - . Ansar; . Cahyawan; . Safrani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
The objectives of this research were to study the characteristics of mango chips drying using a double plated solar collector. The materials used were sliced mangoes with the thickness of 3, 6, and 8 mm. The equipments used for this research were double plated solar collector, thermocouple, digital balance, thermometer, vacuum oven, and desiccators. The research parameters included the rate of heat energy absorbed by the double plated solar collector, the heat energy losses, the efficiency of the double plated solar collector and the moisture content of the chips. The results of this study suggested that the use of double plated solar collector could increase the temperature and the amount of heat energy, thus speed up the drying process of the mango chips. The energy needed to evaporate the moisture content in mango decreased in proportion to the increase in drying time. The difference in mango chips’ thickness resulted in different decrease rate in water content until it reached a constant state. The efficiency of the double plated solar collector was 77.82%.